Utility theory and mean variance - Instefjord, Norvald (Henry Stewart Talks, 2007)
Expected utility representation of preferences, Rationality criteria, State independent utility, Risk averse behavior, Risk and insurance premium, Arrow-Pratt's absolute risk aversion coefficient, Risk aversion and small risk, Relative risk aversion coefficient, Risk tolerance, CARA utility, CRRA utility, Risk aversion and large risk, Utility and variance measures of risk, Variance aversion and two fund separation, Local risk neutrality, Marginal utility and two fund separation, Factor structure and two fund separation
Archived at 2022/04/04